Caries experience among cigarette and e-cigarette users: a 6-month prospective study - Ghazali, Aini Fatimah; Ismail, Ahmad Faisal; Daud, Azlina (PharmaInfo Publications, 2019)
This study aimed to evaluate and compare the caries experience among cigarette smokers, e-cigarette smokers, and non-smokers. This observational study involved 135 participants; with 45 participants in each group respectively. Dental caries was recorded and evaluated using the DMFT score. The results were compared using analysis of variance (MANOVA) for analysis between the groups and the Wilxocon Rank test for analysis within the groups. The outcomes of the analysis were insignificant between the groups (p = 0.370) at baseline and (p =0.480) at the 6-month follow up. The result was significant within the group; cigarette users (p = 0.005), e-cigarette users (p = 0.000), and control group (p = 0.025). In conclusion, cigarette and e-cigarettes usage has potential detrimental effect on caries development. However, more longitudinal studies required to provide more evidences.